Giant cell tumour of the distal radius/ulna: Response to pre-operative treatment with short-term denosumab - McCarthy, C; Gibbons, C; Bradley, K; Hassan, A; Giele, H; Athanasou, N (BioMed Central, 2017)
Background Treatment of giant cell tumour of bone (GCTB) of the distal radius/ulna poses a surgical challenge, as complex reconstructive surgery may be required. This study evaluates the clinical, radiological and pathological findings in five cases of GCTB of the distal forearm where a 3 month course of denosumab was given prior to surgery. Methods Patients with biopsy proven distal forearm GCTB, treated for 3 months with denosumab, followed by salvage surgery (curettage and cementation) were included. Wrist pain and function were assessed using the modified Mayo Wrist Score (MMWS). Plain radiographs, MRI and PET/CT were performed pre-treatment and 2 months after initiation of denosumab therapy. Histological comparison was made between the original biopsy and surgical curettage specimens. Results Five patients with an average age of 25 years were included in the study. Improvement in wrist pain and function was seen in all patients with the average MMWS increasing from 30 pre-treatment to 85 at 3 months. Plain radiographs demonstrated marginal sclerosis in all cases with reconstitution of cortical and subarticular bone by 2 months; internal matrix sclerosis and osseous consolidation was more variable. Increased tumour heterogeneity and low signal were observed on T2-weighted MR images. PET/CT revealed a decrease in average SUV from 14.8 pre-treatment to 4.7 at 2 months. Histology showed disappearance of osteoclasts and increased fibro-osseous tissue. Denosumab treatment has the potential to facilitate salvage surgery, thus avoiding bone resection and graft reconstruction. A good outcome was achieved apart from local recurrence in one case. Follow up ranged from 17 to 54 months. Conclusion Distal forearm GCTB responds clinically, radiologically and histologically to a short course of pre-operative denosumab therapy, which has the potential to facilitate salvage surgery.